PSYCHOLOGICAL MOTIVES IN FITZGERALD’S SHORT STORIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article tells brief about the biography of F. Scott Fitzgerald and psychological motives of his works. F. Scott Fitzgerald is best known as the creator of the flapper in fiction, a chronicler of youth and wealth in the 1920's. His first novel, This Side of Paradise (1920), was influential among college students and was informative to their parents. During the 1920's, popular magazines wanted Fitzgerald-type stories and asked for them by name. His main achievement was in the realm of the serious novel and the short story, something quite apart from his public reputation as Poet Laureate of the Jazz Age. Among those authors admittedly influenced by Fitzgerald are J. D. Salinger and John O'Hara.